Evaluasi Sistem Penerimaan Mahasiswa Baru Pada Masa Pandemi Covid-19 (Studi Kasus di Undiksha Tahun 2021) - I.K.A. Supradnyan; I.K.S. Panca; P. Suadharma; L.N. Aryani (Jurnal Administrasi Pendidikan Indonesia, 2022)
This qualitative descriptive study aims to evaluate the new student admissions system in order to increase the number of students during the Covid-19 pandemic. The focus of this goal is based on the problem, namely the pandemic condition with various social scale restrictions causing the promotion of institutions and the new student admission system to be empowered through online media networks. This research is useful in providing information regarding the new student admission system under the leadership of an Undiksha leader and later being able to make policies regarding the evaluation of this system. The subject of this research is the implementer of the new student admission system. Data were collected through interview, observation, and documentation methods. The results show that there are several new student admission systems at Ganesha Education University to increase the number of students during the Covid-19 pandemic, including through the SMBJM for talent interest, SNMPTN, SBMPTN, and SMBJM (CBT); there are many obstacles experienced by the implementers of the new student admission system when implementing the new student admission system at the Ganesha University of Education during the Covid-19 pandemic, one of which is the internet network that is not the same in coverage in each area so that it can hamper the new student admission system; and the solution that can be given regarding these obstacles is to empower teachers to provide information regarding new student admissions in every SMA/SMK.